2008
DOI: 10.1007/s11695-008-9517-8
|View full text |Cite
|
Sign up to set email alerts
|

One-year Readmission Rates at a High Volume Bariatric Surgery Center: Laparoscopic Adjustable Gastric Banding, Laparoscopic Gastric Bypass, and Vertical Banded Gastroplasty-Roux-en-Y Gastric Bypass

Abstract: Rates of readmissions for patients undergoing bariatric surgery center at our high-volume center decreased over time and are comparable to other major abdominal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
2
29
2
Order By: Relevance
“…For example, BMI was not recorded in the discharge data and although it can be assumed that all patients met the criteria for morbid obesity, the effect of BMI on operative outcomes could not be ascertained. Readmission beyond 30 days was not captured within this study, though evidence shows the most resource-intensive admission occurs within the first 30 days [16,31]. There was also heterogeneity between centers and surgeon practices which could not be controlled for though all centers met criteria for OBN center of excellence designation previously described [24].…”
Section: Discussionmentioning
confidence: 91%
“…For example, BMI was not recorded in the discharge data and although it can be assumed that all patients met the criteria for morbid obesity, the effect of BMI on operative outcomes could not be ascertained. Readmission beyond 30 days was not captured within this study, though evidence shows the most resource-intensive admission occurs within the first 30 days [16,31]. There was also heterogeneity between centers and surgeon practices which could not be controlled for though all centers met criteria for OBN center of excellence designation previously described [24].…”
Section: Discussionmentioning
confidence: 91%
“…Both figures were significantly higher when compared to the 1.2 % readmission rate of the laparoscopic adjustable gastric band (LAGB). Saunders et al [7] in an analysis of 1939 bariatric procedures found that 18.8 % required hospital readmission within the first year after surgery. Laparoscopic Roux-en-Y gastric bypass (LRYGB) had a readmission rate of 24.2 %, and the LAGB had the lowest readmission rate (12.69 %).…”
Section: Discussionmentioning
confidence: 99%
“…Doumouras et al [35] reported a readmission rate of 6.1% over a period of 3 years. Saunders et al [36] reported 1-year readmission rate of 18.8%. …”
Section: Introductionmentioning
confidence: 99%